2022
DOI: 10.1002/ppul.25824
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of lung oxygenation by near‐infrared spectroscopy in preterm infants with respiratory distress syndrome: A proof‐of‐concept study

Abstract: Introduction: Noninvasive markers more accurate than FiO 2 would be useful to assess the severity of RDS and guide its treatment. Our aim was to assess for the first time the possibility of continuously monitoring lung oxygenation (rSO 2 L) by near-infrared spectroscopy (NIRS) and to evaluate whether rSO 2 L correlates with other oxygenation indices and RDS severity. Methods:We carried out this proof-of-concept study on 20 preterm infants with RDS requiring noninvasive respiratory support. Patients were contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 36 publications
(69 reference statements)
1
18
0
Order By: Relevance
“…A recent study evaluated postnatal pulmonary oxygenation in 20 preterm infants within the first 24 h of life and demonstrated that regional pulmonary oxygenation was correlated with other oxygenation indices such as SpO 2 /FiO 2 , arterial/alveolar oxygen tension ratio (a/AO 2 ) and oxygenation index (O.I). The authors concluded that continuous monitoring of rSO 2 of lung in preterm infants was feasible and correlated with other reliable indices of oxygenation and RDS severity 11 . Apart from this study, there exists no data about the early pulmonary oxygenation in late preterm and term newborn infants with respiratory distress.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…A recent study evaluated postnatal pulmonary oxygenation in 20 preterm infants within the first 24 h of life and demonstrated that regional pulmonary oxygenation was correlated with other oxygenation indices such as SpO 2 /FiO 2 , arterial/alveolar oxygen tension ratio (a/AO 2 ) and oxygenation index (O.I). The authors concluded that continuous monitoring of rSO 2 of lung in preterm infants was feasible and correlated with other reliable indices of oxygenation and RDS severity 11 . Apart from this study, there exists no data about the early pulmonary oxygenation in late preterm and term newborn infants with respiratory distress.…”
Section: Discussionmentioning
confidence: 74%
“…Although the penetration depth of 1.0-1.5 cm of NIRS light is appropriate to assess the oxygenation of lung parenchyma, there is a concern about whether NIRS can measure oxygenation of a non-solid air filled tissue accurately. 11 The first study that reveals the oxygenation of lung parenchyma showed that NIRS is technically able to assess quantitatively tissue oxygenation of lung tissue both in vivo and in vitro medium. 20 One of the pioneer clinical study evaluating the regional oxygenation of lung areas was performed by Yang et al They evaluated regional pulmonary oxygenation in 26 preterm infants and reported that NIRS objectively reflected the changes in oxygenation in the lung tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations